Impact of two thermal processing routes on protein interactions and acid gelation properties of casein micelle-pea protein mixture compared to casein micelle-whey protein one. (May 2022) - Beghdadi, Abdessalem; Picart-Palmade, Laetitia; Cunault, Charles; Marchesseau, Sylvie; Chevalier-Lucia, Dominique
Graphical abstract: Highlights: Thermal processing influences casein micelle-pea protein mixture properties. Heat treatment induces size decrease and hydrophobicity increase of pea aggregates. Heat-treated casein micelle-PP acid gels were firmer than casein micelle-WP ones. PP aggregates and CM in mixture formed independent gels during acidification. Abstract: The influence of two heating protocols (protocol 1 and 2) on protein interactions and acid-induced gelation properties of casein micelle-pea protein mixture (CM-PP) was investigated and then compared to casein micelle-whey protein mixture (CM-WP). The CM:PP and CM:WP protein weight ratio for mixtures was 7.5:2.5, for a total protein content of 4% (pH 6.7). Protocol 1 consisted of a heat treatment (85 °C for 1 h) of CM-PP and CM-WP mixtures, respectively. Regarding protocol 2, casein micelle, pea protein and whey protein stock dispersions were individually pretreated by heating (85 °C for 1 h) before the mixtures were made and heated in the same conditions of protocol 1 (85 °C for 1 h). Heat pretreatment carried out in the protocol 2 significantly increased PP hydrophobicity and reinforced weak interactions of the initial pea protein particles. This pretreatment on protein stock dispersions led to twofold smaller pea protein particles compared to whey protein aggregates. The hydrophobic interactions between pea proteins and casein micelles promoted by the two heating protocols have greatly contributed to improve acid gelation functionalities of CM. Regardless of the heating protocol, acid-induced gelation of the CM-PP mixtures led to the formation of gel networks with a significant increase in stiffness and firmness compared to casein micelle or CM-WP mixtures gels.